The Development and the Application of the Microbial Enzymes: Take the Polar Microbial Enzymes as an Example - Yang, Jiaxuan (International Journal of Natural Resources and Environmental Studies, 2025)
This article systematically explores the development history, current application status and future prospects of microbial enzymes, with a particular focus on the unique structure and function of polar microbial enzymes. The aim is to break through the technical bottlenecks of traditional enzyme preparations and explore their innovative application potential in the industrial field.